EFEK MODERASI DUKUNGAN TEMAN SEBAYA PADA PENGARUH DISIPLIN BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI - Dwi Nur Septyorini, - (2020)
This study is based on many students get the learning outcomes which is still less than the Minimum Criteria on economic subjects in class XI Social Sciences of state Senior High Schools in Tasikmalaya City, this can be seen from the results of the final semester assessment obtained by student. The purpose of this study was to determine the effect of learning discipline on learning outcomes in economic subjects with peer support as a moderator variables. The method used in this study is the survey using questionnaires distributed online through google forms as a tool for data collection. The data analysis technique used is multiple linier regression through multiple regression analysis with moderator variable. The population in this study of 378 student, using a random sampling techniques, this study selected 194 students as a sample. The results show that: (i) the level of student discipline is in the high category; (ii) the level of learning discipline has a positive and significant effect on the level of learning outcomes; (iii) peer support does not effecting moderate the effect of learning discipline on learning outcomes. The Implications of this study, to improve student learning outcomes in senior high school are discussed.